RADIKALISME DAN TERORISME AGAMA, SEBAB DAN UPAYA PENCEGAHAN - Ahmad Syafi’i Mufid (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2013)
The terrorists arrested, put in trial, or sentenced, as well as their supporters, have stated that what they did (terror) was jihad fi sabilillah. Struggle with violence and terror has been perceived as a holy jihad, robbery has been considered as fa’i, and self-explosion (suicide bombing) has been believed as syahid (amaliyah al istisyhad). The radicalism of this group of people will keep on growing and developing as long as the ambition of establishing daulah Islamiyah or khilafah ala minhaj al nubuwah is not achieved yet. Nevertheless, radicalism and terrorism views and movements have been possibly changed as their ideologists have shown an openness. Dr. Najih Ibrahim and Dr. Karom Zuhdi’s experience in Egypt is good to be a model on how jihad ideology, such as Al-Jama’ah Al Islamiyah in Egypt, underwent reinterpretation as well as awareness that past struggles have never been successful, and even contraproductive. This kind of change can be copied and developed in Indonesia by creating dialogue opportunities for radical thinkers and moderate Ahlu Sunnah wal Jama’ah. Indonesian Council of Islamic Scholars (MUI) is expected to be a coordinating host for them by activating associational networks as well as muslims’ daily networks.